Evaluation of topical potassium hydroxide solution for treatment of plane warts - Khalil I Al-Hamdi; Moutaz AA AL-Rahmani (Wolters Kluwer Medknow Publications, 2012)
Background: Plane wart is a common dermatological disease that is caused by human papilloma virus; although the rate of spontaneous recovery is high, it usually takes a long time to occur. Many modalities of treatments have been used but none of them proved to be uniformly effective. Potassium hydroxide (KOH) solution is a well-known keratolytic agent with many dermatological uses. Objective: To evaluate the efficacy and tolerability of topical KOH solution in the treatment of plane warts. Materials and Methods: A total of 250 patients with plane warts, consulting the department of Dermatology and Venereology of Basra Teaching Hospital between March 2008 and October 2009, were enrolled in this opened therapeutic trial study. Patients were divided into two age and sex cross-matched equal groups; patients in group (A) were treated with topical 5% KOH solution once at night, while patients in group (B) were treated with topical 10% KOH solution once nightly. Only 107 patients from group (A) and 95 patients from group (B) completed the study, while the remainders were defaulted for unknown reasons. The patients were evaluated at second and fourth week to assess the cure rates and side effects, those patients who showed complete cure were followed up for 3 months to detect any recurrence. Results: At the end of second week, 9.3% of group (A) patients showed complete disappearance of their warts, vs 66.3% of group (B) patients. At the end of fourth week, 80.3% of group (A) patients showed complete response in comparison with 82.1% of group (B) patients. The side effects for the treating solution in both concentrations include itching, burning sensation, erythema, and temporary dyspigmentations, that were reported in 77.6% of group (A) patients in comparison with 90.5% of group (B) patients. Recurrence rate was reported in 5.8% of group (A) patients vs 5.1% of group (B) patients during the three months period of follow-up. Conclusions: Topical KOH solution is proved to be an effective and safe treatment of plane warts in both concentrations (5% and 10%) with no important side effects.